Chemical Quality Analysis of Male Quick Meat with Rate Containing Fermented Rice Bran - I Gusti Ayu Dewi Seri Rejeki; Ni Ketut Mardewi; Ni Ketut Sri Rukmini; A A Sagung Putri Risa Andriani; S A M P Suryani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Abstract. Quail is a small but fat land fowl. One of the most popular types of quail is the quail (Coturnix coturnix japonica). Quail is a diversified source of meat and egg products. In raising quail, the cost of feed is very high, reaching 70% of the total cost of quail production. Rice bran is an industrial waste that still has a high enough nutritional value but has the disadvantage that it contains high fiber, to overcome this, it needs to be fermented to improve the quality of the feed ingredients. The protein content of rice bran ranges from 8 -12%, rice bran is very taken into account in the preparation of poultry rations. This study used a completely randomized design with 5 treatments and 3 replications. Each replication consisted of 3 quail so the number of quail used was 45. The treatments were as follows: P0 = Treatment of 100% artificial ration, P1 = Treatment of 95% ration + 5% fermented rice bran, P2 = Treatment of 90% ration + 10% fermented rice bran, P3 = Treatment of 85% ration + 15 % fermented rice bran, P4 = treatment 80% ration + 10% fermented rice bran. The data obtained will be analyzed using variance and if between treatments shows a significant effect, then proceed with Duncan's New Multiple Range Test (DNMRT).. The results showed that the provision of rations containing fermented rice bran had no significant effect (P>0.05) on the variables of Protein Content, Cooking Loss, and Water Holding Capacity, while the water content variable showed significant results (P<0.05). At the level of administration, 20% fermented rice bran produced the optimal chemical quality of male quail meat.